2017
DOI: 10.1002/pi.5464
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan for wastewater treatment

Abstract: Chitosan (an amino-polysaccharide obtained from deacetylation of chitin, the major constituent of crustaceous shells and insect cuticles) presents a cationic character in acidic media allowing its dissolution, its shaping and possible ion-exchange interactions with anionic compounds (a property applied in adsorption and coagulation-flocculation processes). In neutral media, non-protonated amino groups allow complexation of metal cations or organic chemicals. These different properties explain the interest take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(71 citation statements)
references
References 62 publications
1
66
0
4
Order By: Relevance
“…In the past two decades, these materials used as biosorbents have received much attention in water and wastewater treatment, mainly for metal chelation and dye removal Crini 2015;Kos 2016;Muya et al 2016;Kanmani et al 2017;Kyzas et al 2017;Nechita 2017;de Andrade et al 2018;Desbrières and Guibal 2018;El Halah et al 2018;Pakdel and Peighambardoust 2018;Wilson and Tewari 2018). Indeed, chitosan has an extremely high affinity for metals and metalloids and for many classes of dyes, including direct, acid, mordant and reactive.…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past two decades, these materials used as biosorbents have received much attention in water and wastewater treatment, mainly for metal chelation and dye removal Crini 2015;Kos 2016;Muya et al 2016;Kanmani et al 2017;Kyzas et al 2017;Nechita 2017;de Andrade et al 2018;Desbrières and Guibal 2018;El Halah et al 2018;Pakdel and Peighambardoust 2018;Wilson and Tewari 2018). Indeed, chitosan has an extremely high affinity for metals and metalloids and for many classes of dyes, including direct, acid, mordant and reactive.…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
“…Indeed, chitosan has an extremely high affinity for metals and metalloids and for many classes of dyes, including direct, acid, mordant and reactive. In their comprehensive reviews, Crini (2015), Yong et al (2015), Kyzas et al (2017), Wang and Zhuang (2017), Desbrières andGuibal (2018), El Halah et al (2018) and Pakdel and Peighambardoust (2018) recently indicated that biosorption onto chitosan was a promising alternative to replace conventional adsorbents used for decolorization purposes, metal chelation or recovery, and organic removal. With nutraceuticals and cosmeceuticals, the water and wastewater treatment field seems to be the next market in the development of chitosan (Morin-Crini et al 2019).…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
“…Indeed, chitosan has an extremely high affinity for metals and metalloids and for many classes of dyes, including direct, acid, mordant and reactive. In their comprehensive reviews, Crini (2015), Yong et al 2015, Kyzas et al (2017), Wang and Zhuang (2017), Desbrières andGuibal (2018), El Halah et al (2018) and Pakdel and Peighambardoust (2018) recently indicated that biosorption onto chitosan was a promising alternative to replace conventional adsorbents used for decolorization purposes, metal chelation or recovery, and organic removal. With nutraceuticals and cosmeceuticals, the water and wastewater treatment field seems to be the next market in the development of chitosan.…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
“…type of functional groups and degree of grafting but also to textural properties (from microspheres to nanoparticles). An overview of the literature data shows that performances strongly depend on the type of material used (Crini 2015;Yong et al 2015;Kyzas et al 2017;Wang and Zhuang 2017;Desbrières and Guibal 2018). Indeed, each material has its specific application as well as inherent advantages and disadvantages in dye removal.…”
Section: Biosorption Capacitymentioning
confidence: 99%
“…Crini thus spoke of two-in-one materials (Crini and Badot 2007;Crini et al 2009a, b). Several recent reviews have demonstrated that direct bioflocculation is an effective and competitive approach, and that chitosan is a promising bioflocculant for environmental and purification purposes (Chong 2012;Lee et al 2014;Crini 2015;Bhalkaran and Wilson 2016;Laamanen et al 2016;Yang et al 2016;Kanmani et al 2017;Ummalyma et al 2017;Wang and Zhuang 2017;Desbrières and Guibal 2018;Pakdel and Peighambardoust 2018;Song et al 2018;Salehizadeh et al 2018, Van Tran et al 2018Crini et al 2019;Vidal and Moares 2019).…”
Section: Introductionmentioning
confidence: 99%